Medical education: an Italian contribution to the discussion on global health education - Giulia Civitelli; Gianfranco Tarsitani; Alessandro Rinaldi; Maurizio Marceca (BMC, 2020)
Abstract Background In Italy an important contribution to the spread of global health education (GHE) grew from the establishment and work of the Italian Network for Global Health Education (INGHE). INGHE gave a national shared definition of global health (GH), grounded in the theory of determinants of health, inspired by a vision of social justice, and committed to reduce health inequities. The aim of this article is to share with the international community INGHE's point of view on Medical Education. Methods To express its view of medical education at the national level, INGHE established a dedicated commission, which elaborated a first draft of the document and then shared and discussed it with all other members. Results INGHE elaborated a paper where it explained the need to change medical education in order to prepare future health professionals for the challenges of the globalized and unequal world. In this article the authors summarize the experience of INGHE and share with the international community its document. Conclusions The authors believe it is necessary now, more than ever, to insert this new approach to health at social and academic levels. Students should play a fundamental role in the spread of GHE, and activities related with GHE could be considered an important part of the third mission of universities to promote social justice.